Seaweed and mangrove issues from International Law perspective - Hamid, Abdul Ghafur@Khin Maung Sein (2012)
Since Malaysia is a coastal State with invaluable mangroves and atolls and coastal areas, surrounded by resource-rich seas, to make the Malaysian maritime areas to be clean and pollution-free is a matter of grave concern for the country. Seaweed farming in Malaysia can possibly be governed by the Fisheries Act. What we need is to adopt a new “Fisheries (Seaweed Farming) Regulations” under s. 61 of the Fisheries Act to regulate seaweed farming in Malaysia. The protection and preservation of mangrove forests need integrated cooperation among the various government agencies. The protection and preservation of mangrove forests need integrated cooperation among the various government agencies. Although we have National Forestry Act 1984, It is proposed that it should be amended to include specific provisions for the protection and preservation of mangroves.